USLE‑Based Spatial Analysis of Soil Erosion Risk in the Brangkal Sub‑Watershed, Mojokerto - Dimas Prabowo Harliando; Zumrotun Yogi Noviana; Ulfa Rizkika Mufadhila; Dewi Shasa Belia (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2025)
Soil erosion in upland watersheds reduces land productivity, degrades water quality, and threatens ecological services, particularly in areas undergoing tourism‑driven land‑use change. This study quantified and mapped soil erosion in the Brangkal Sub-Watershed, with a focus on the Pacet Hills tourism area in Mojokerto, East Java. The study employed the Universal Soil Loss Equation (USLE) in combination with ArcGIS, incorporating rainfall erosivity (R), soil erodibility (K), slope length–steepness (LS), land cover (C), and conservation practice (P). Rainfall erosivity was derived from five‑year precipitation records using the Lenvain method, soil erodibility from laboratory‑analyzed texture and organic matter, LS from a 30 m DEM, and CP from land‑use classification adjusted with field observations. All factors were rasterized and multiplied cell‑by‑cell in ArcGIS to generate annual soil loss estimates and hazard maps. Results indicated annual soil loss between 7.24 and 1922.75 ton ha⁻¹ yr⁻¹, with severe erosion concentrated in steep, intensively cultivated upper‑catchment zones where LS and CP values are high. Field‑derived and reference K values were in close agreement, validating the reliability of hotspot identification. Soils, dominated by Andisols and Inceptisols, exhibited moderate to high erodibility, especially under reduced vegetation cover. Recommended management priorities are vegetative reinforcement, structural slope stabilization, nutrient and pH correction, and land‑use zoning to minimize disturbances in high‑risk areas. The integration of USLE and GIS provides a robust framework for prioritizing conservation actions that protect soil resources while sustaining the ecological and tourism value of Pacet Hills.